INTEGRATING GOOGLE CLASSROOM INTO EFL WRITING INSTRUCTION IN ACADEMIC LYCEUMS: STAGES OF DEVELOPMENT BASED ON THE ADDIE MODEL - Usmanova Shokhsanam Avazovna (International Journal of Literature and Language Studies, 2026)
The integration of digital technologies into language education has become an important aspect of modern teaching practice. This study examines the stages of developing Google Classroom-based instruction for English language lessons in academic lyceums. The research applies the ADDIE instructional design model to organize the integration of Google Classroom into EFL writing instruction. The study analyzes learner needs, technological readiness, and institutional requirements, and proposes a structured instructional model combining offline teaching with digital support. Findings demonstrate that systematic application of the ADDIE model helps align digital tools with curriculum objectives and improves opportunities for collaborative writing, feedback, and learner engagement.